2012
DOI: 10.1186/1755-8794-5-46
|View full text |Cite
|
Sign up to set email alerts
|

Defining the genomic signature of the parous breast

Abstract: BackgroundIt is accepted that a woman's lifetime risk of developing breast cancer after menopause is reduced by early full term pregnancy and multiparity. This phenomenon is thought to be associated with the development and differentiation of the breast during pregnancy.MethodsIn order to understand the underlying molecular mechanisms of pregnancy induced breast cancer protection, we profiled and compared the transcriptomes of normal breast tissue biopsies from 71 parous (P) and 42 nulliparous (NP) healthy pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
93
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(104 citation statements)
references
References 48 publications
11
93
0
Order By: Relevance
“…As a demonstration that PRM can be used to initially verify candidate phosphoproteins, we selected four phosphoproteins: Ral GTPase-activating protein subunit alpha-2 (RALGAPA2), cGMP-dependent protein kinase1 (PKG1), tight junction protein 2 (TJP2), and nuclear transcription factor, X box-binding protein 1 (NFX1). These four proteins showed significant phosphorylation up-regulation in patients with cancer, were previously reported as phosphoproteins, and have been implicated in multiple breast cancer studies (23)(24)(25)(26).…”
Section: Verification Of Phosphorylation Specific To Patients With Camentioning
confidence: 74%
“…As a demonstration that PRM can be used to initially verify candidate phosphoproteins, we selected four phosphoproteins: Ral GTPase-activating protein subunit alpha-2 (RALGAPA2), cGMP-dependent protein kinase1 (PKG1), tight junction protein 2 (TJP2), and nuclear transcription factor, X box-binding protein 1 (NFX1). These four proteins showed significant phosphorylation up-regulation in patients with cancer, were previously reported as phosphoproteins, and have been implicated in multiple breast cancer studies (23)(24)(25)(26).…”
Section: Verification Of Phosphorylation Specific To Patients With Camentioning
confidence: 74%
“…The genomic profile of nulliparous and parous women in the premenopausal and postmenopausal period has shown that there are genes which are only activated during the first five years after pregnancy that may contribute to the increased risk experienced by certain women after pregnancy [28,47,48,72]. At the same time pregnancy induces a long lasting genomic signature that starts after pregnancy, explaining its preventive effect.…”
Section: Discussionmentioning
confidence: 99%
“…The morphological, physiological and genomic changes resulting from pregnancy and hormonally-induced differentiation of the breast and their influence on breast cancer risk have been addressed above and in the literature [43][44][45][46][47][48]. The observations that during the postmenopausal years the breasts of both parous and nulliparous women contain predominately Lob 1, and the fact that nulliparous women are at higher risk of developing breast cancer than parous women, indicate that Lob 1 in these two groups of women either differ biologically, or exhibit different susceptibility to carcinogenesis [46].…”
Section: Cellular and Molecular Basis Of The Protective Effect Of Earmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also our understanding that this is the first study to assess parity-related changes in normal human breast tissue stratified according to early and late parity, as well as, nulliparity. Many prior studies have assessed changes at the transcript level in parous versus nulliparous populations [4,19,21,22]. The study design we have implemented here is critical for assessing changes in the mammary gland that truly play a role in parity-related breast cancer protection.…”
Section: Discussionmentioning
confidence: 99%